Visual thinking in teaching history: Reading the visual thinking skills of 12 year-old pupils in Istanbul - (:unkn) unknown (My University, 2010)
This study aims to explore the visual thinking skills of some sixth grade (12-13 year-old) primary pupils who created visual interpretations during history courses. Pupils drew pictures describing historical scenes or events based on visual sources. They constructed these illustrations by using visual and written primary and secondary sources in two different history courses; data in this study were collected using a qualitative action research approach. A sample of drawings which demonstrated sufficient historical and visual thinking skills was selected for analysis. These data were analysed using predetermined criteria based on the processes of historical and visual thinking. Results show that drawings are an effective way of accessing pupils' historical thinking and that art work which visualises the past supports historical problem solving. The purpose of this paper is to understand how images as historical sources are transformed into images as products of the process of historical thinking. The study focuses on how pupils can, through historical thinking, translate visual sources into pupils' illustrations of past events. First, the relationship between visual thinking, visualisation of the past, and historical imagination was studied. Then historical illustrations constructed by the students were analysed to try to understand how the process of visualisation relates to the process of learning in history. © 2010 ASPE.
Keywords: Historical imagination; Historical thinking; Pupils' illustrations; Visual thinking